(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The results of the study carried out during 2009-2010 with lablab bean (Lablab purpureus) are presented in this paper. Data were recorded from all experimental plants on the following characters as number of pods/plant, pod yield/plant (g), number of seeds/pod, number of seeds/plant; seed yield/plant (g), Range, mean, genetic parameter, correlation co-efficient and path coefficient were studied. High heritability coupled with high expected genetic advance in percentage of mean were observed for most of the characters. The coefficients of correlation showed that seed yield/plant was positively and significantly correlated with days to first flowering, days to 50% flowering, days to first pod setting, number of pods/plant, pod yield/plant and seeds/pod, number of seeds/plant, and seed yield. Path coefficient analysis showed that days to first flowering, days to 50% flowering, number of pods/plant, 20 pod weight (g), pod yield/plant, pod length, number of seeds/pod, number of seeds/plant, 100-seed weight influenced seed yield/plant directly in positive direction. Among the characters, number of seeds/plant had high positive correlation with seed yield/plant. Days to first pod setting exhibited negative direct effects on seed yield. From this result, it can be concluded that days to first flowering, days to 50% flowering, number of pods/plant, pod yield/plant, number of seeds/pod, number of seeds/plant, 100-seed weight are the most important yield contributing characters as they influenced pod yield and seed yield directly in positive direction. DOI: http://dx.doi.org/10.3329/bjar.v38i4.19662 Bangladesh J. Agril. Res. 38(4): 705-717, December 2013